1998
DOI: 10.1002/(sici)1521-4141(199812)28:12<4188::aid-immu4188>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Production of reactive oxygen intermediates following CD40 ligation correlates with c-Jun N-terminal kinase activation and IL-6 secretion in murine B lymphocytes

Abstract: Recent studies indicate that reactive oxygen intermediates (ROI) serve as second messengers in cell signaling. ROI have been implicated in the activation of NF-kappaB as well as c-Jun N-terminal kinase (JNK) in response to IL-1 and TNF-alpha stimulation. In this report we examine whether intracellular ROI are involved in CD40 receptor signaling. We show that CD40 engagement on resting splenic B lymphocytes and murine B lymphoma WEHI 231 cells generates ROI. Blocking ROI production by preincubation with the ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 48 publications
4
65
2
Order By: Relevance
“…On the basis of our data, we propose that CD40 stimulation sensitizes CLL cells to rituximab-mediated death by increasing basal ROS production, which is further increased by rituximab. ROS production after CD40 stimulation has been described before in B cells, 57 and CD40-induced ROS have critical roles in CD40-mediated B-cell regulation, for example, nuclear factor-kB signaling. 58 Our data indicate that constitutive CD40 signaling results in activation of CLL cells and increased basal ROS production.…”
Section: Discussionmentioning
confidence: 65%
“…On the basis of our data, we propose that CD40 stimulation sensitizes CLL cells to rituximab-mediated death by increasing basal ROS production, which is further increased by rituximab. ROS production after CD40 stimulation has been described before in B cells, 57 and CD40-induced ROS have critical roles in CD40-mediated B-cell regulation, for example, nuclear factor-kB signaling. 58 Our data indicate that constitutive CD40 signaling results in activation of CLL cells and increased basal ROS production.…”
Section: Discussionmentioning
confidence: 65%
“…Moreover, pharmacological inhibitors of JNK have been shown to confer protection from apoptosis in a human B cell line (39). In contrast, studies have shown that CD40-mediated signaling and treatment of B cells with CpG DNA, both of which exert potent anti-apoptotic effects, potently induce activation of JNK (55)(56)(57). However, it should be noted that activation of JNK under these conditions does not appear to be required for the protective effect of these pro-survival agonists (55)(56)(57).…”
Section: Discussionmentioning
confidence: 99%
“…Maintenance of the WEHI 231 mouse B lymphoma line and isolation of splenic B cells were described previously (11). When stimulated, the cells *Division of Molecular Life Sciences and Center for Cell Signaling Research, and † Department of Life Science, College of Natural Sciences, Ewha Womans University, Seoul, Korea (WEHI 231: 5 ϫ 10 5 /ml, splenic B cells: 1 ϫ 10 6 /ml) were incubated with anti-CD40 mAb (R&D Systems, Minneapolis, MN) at 1 g/ml for indicated times.…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%
“…The cells were transfected with 40 g of the vector, or the indicated expression plasmid DNA, along with 5 g of the GFP plasmid for immunocytochemistry. Reporter gene assays were performed as described previously (11) and luminescence was determined using Luminoskan TL Plus (Bio-Orbit, Turku, Finland).…”
Section: Transient Transfections and Reporter Gene Assaymentioning
confidence: 99%